2017
DOI: 10.1111/odi.12614
|View full text |Cite
|
Sign up to set email alerts
|

Immune reactivity after adenoviral‐mediated aquaporin‐1 cDNA transfer to human parotid glands

Abstract: OBJECTIVES The purpose of this study was to examine the humoral and cellular immune reactivity to adenoviral vector (AdhAQP1) administration in the human parotid gland over the first 42 days of a clinical gene therapy trial. METHODS Of eleven treated subjects, five were considered as positive responders (Baum et al, 2012). Herein, we measured serum neutralizing antibody titers, circulating cytotoxic lymphocytes, and lymphocyte proliferation in peripheral blood mononuclear cells. Additionally, after adenovira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…No sample was available to perform this assay at the second follow-up visit of subject 19. The exact days of each follow-up visit are listed in the legends of Figures 1 and 3 , and Table 1 .Note that serum neutralizing antibody titers found in all time points through day 42 have recently been reported and were generally similar to those shown in the figure 16 .…”
Section: Figuresupporting
confidence: 63%
See 1 more Smart Citation
“…No sample was available to perform this assay at the second follow-up visit of subject 19. The exact days of each follow-up visit are listed in the legends of Figures 1 and 3 , and Table 1 .Note that serum neutralizing antibody titers found in all time points through day 42 have recently been reported and were generally similar to those shown in the figure 16 .…”
Section: Figuresupporting
confidence: 63%
“…Previously, we have reported serum neutralizing antibody (NAb) levels at baseline 12 and over the initial 42 days post-AdhAQP1 treatment 16 . As shown in Figure 4 , compared to baseline serum NAb levels measured in the five responder-subjects, little change occurred throughout the study, extending to 3+ years post-treatment, with serum NAb titers at or below those measured at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Adenovirus-mediated hAqp1 gene transfer restored both salivary and lacrimal secretion and decreased local and systemic inflammation in a SS mouse model induced by BMP6 overexpression [ 151 ]. A phase I clinical trial (NCT00372320) revealed that adenoviral vector encoding hAqp1 improved saliva secretion in six out of eleven patients suffering from SG hypofunction post-irradiation therapy [ 152 ], and that this improvement persisted for 3 to 4.7 years post-administration [ 153 ]. Five of the six responders also showed improvements in subjective perception of oral dryness and amount of saliva present in the mouth by visual scale assessment [ 152 ].…”
Section: Therapeutic Strategies Aiming At Aqps To Treat Xerostomiamentioning
confidence: 99%
“…Nevertheless, phase I clinical trial reported that in patients with salivary hypofunction resulting from radiation therapy, the administration of adenoviral vector encoding hAQP1 was able to induce rapid (within 42 days) saliva secretion improvement, in five patients out of the eleven patients included [ 93 ], that persisted even 3 to 4.7 years post-administration [ 94 ]. While modest systemic cell-mediated immune reactivity (2–3 fold) did not preclude responses to gene transfer within the five responding patients, a more important change impeded the efficacy of gene transfer in the remaining patients [ 95 ]. Despite its overall safety, the use of AdhAQP1 appears limited by the host immune response.…”
Section: Role Of Aqps In the Treatment Of Sjögren’s Syndromementioning
confidence: 99%